Analisis Potensi Ekonomi Kabupaten Ponorogo dengan Metode Location Quotient dan Shift Share Tahun 2011-2015 - Wahyudi, Eko; , Drs. Yuni Prihadi Utomo, MM (2017)
This researchwill view the development of contributonof sectors in Ponorogo Regency. Knowing the development of the sectors owned can give a description on the economic potential in Ponorogo Regency. The potential is then needed to be prioritized in the economic activities conducted, therefore, the ability to compete with other regions will be stronger. The approach of this researchused two method: Analysis of Location Quotientand Analysis of Shift Share by using secondary data, they are Gross Regional Domestic Product (Produk Domestik Regional Bruto (PDRB))obtained from the Central Statistics Bureau that were secondary statistical data in 2011-2015. This research will discuss about the economic development of Ponorogo, a sector of the base and also potential sectors in Ponorogo. The discussion of this research aims to know the development of GDP Ponorogo, knowing the development sector of the base and potential sectors in Ponorogo. By knowing the sekor development sectors that are owned as well as find out what potential sectors are expected to be able to facilitate the implementation of the development in Ponorogo. Based on the research, it was known that there were eight economic sectors in Ponorogo Regency which were the basic sectors. Those sectors were: agricultural sector, forest and fishing, information and communication sector, financial service and insurance sector, government administration sector, defense and obligatory social insurance, educational service sector, health service and social activity sector, and other service sectors. Meanwhile, for the analysis of Shift Share, it was obtained the result of Nj during 2011-2015 that showed a positive score. It meant that the development of all sectors in Ponorogo Regency is still influenced by the sectors in Province.Meanwhile, for the analysis of Pj, it showed that there were eight sectors which development led to the fast grown sector in Province. The eight sectors were: mining and excavation sector, transportation and warehouse sector, accommodation service and food beverage sector, information and communication sector, financial service and insurance sector, real estate sector, educational service sector, and health service and social activity sector. From the analysis of Dj based on the development of observation from year to year during the researchperiod, it was found that there were seven sectors that have a competitive power revealed by faster growth than similar sectors in the provincial level. The seven sectors were: the electricity and gas service, merchant and retail, car and motorcycle repair, transportation and warehouse sector, information and communication sector, and real estate sector. The harmony of the two analysis tools provided the description on which sectors were the potential sectors. Keywords: Economic Potential, the development of economic sectors, economic base, national share, proportional share, differential share